Tacky Elastomers to Enable Tear‐Resistant and Autonomous Self‐Healing Semiconductor Composites - Zhang, Song; Cheng, Yu‐Hsuan; Galuska, Luke; Roy, Anirban; Lorenz, Matthias; Chen, Beibei; Luo, Shaochuan; Li, Yen‐Ting; Hung, Chih‐Chien; Qian, Zhiyuan; St. Onge, Peter Blake Joseph; Mason, Gage T.; et al. (Advanced functional materials, 2020)
Mechanical failure of π‐conjugated polymer thin films is unavoidable under cyclic loading conditions, due to intrinsic defects and poor resistance to crack propagation. Here, the first tear‐resistant and room‐temperature self‐healable semiconducting composite is presented, consisting of conjugated polymers and butyl rubber elastomers. This new composite displays both a record‐low elastic modulus (<1 MPa) and ultrahigh deformability with fracture strain above 800%. More importantly, failure behavior is not sensitive to precut notches under deformation. Autonomous self‐healing at room temperature, both mechanical and electronic, is demonstrated through the physical contact of two separate films. The composite film also shows device stability in the ambient environment over 5 months due to much‐improved barrier property to both oxygen and water. Butyl rubber is broadly applicable to various p‐type and n‐type semiconducting polymers for fabricating self‐healable electronics to provide new resilient electronics that mimic the tear resistance and healable property of human skin. A mechanically durable and electronically stable semiconducting composite is engineered by introducing a blend of donor–acceptor polymer and butyl rubber elastomer. The composite exhibits ultralow modulus, ultrahigh deformability, tear resistance, and self‐healing performance, as well as ambient stable device stability. This method is widely applicable to different semiconducting polymers.